Preparation method for optimizing olivine type positive electrode material by using surfactant

Through CTAB-induced solvothermal reaction and carbon doping technology, the problems of lithium ion diffusion and insufficient electron conductivity of the olivine-type cathode material are solved, and high specific capacity and excellent electrochemical performance are achieved.

CN119176534AInactive Publication Date: 2024-12-24OCEAN UNIV OF CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411384288.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The electrochemical performance of olivine-type positive electrode materials is limited by the problems of low diffusion coefficient of lithium ion and poor electronic conductivity, and a single optimization strategy is difficult to meet the improvement of electrochemical performance.

Method used

Using the surfactant CTAB as an inducer, an optimized olivine-type positive electrode material is formed through solvothermal reaction. CTAB not only induces crystal surface optimization growth, but also serves as a carbon source to form an N-element doped carbon layer during sintering to improve electron conductivity. sex.

Benefits of technology

Effectively shorten the transmission distance of lithium ions, improve the electrochemical performance of olivine-type positive electrode materials, especially at 1C, and significantly improve the rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176534A_ABST
    Figure CN119176534A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method for optimizing an olivine type positive electrode material by using a surfactant cetyl trimethyl ammonium bromide (CTAB). The preparation process of the method mainly comprises the following steps: S1, adding a Li source, a Fe source, a Mn source, a P source and a surfactant into a reaction kettle according to a ratio; s2, performing solvothermal reaction by taking water and a diethylene glycol solution as solvents to obtain a precursor; and S3, mixing the precursor powder with a carbon source, and sintering to obtain the olivine type positive electrode material optimized by using the surfactant. In the invention, the addition of the surfactant can induce the crystal orientation preferred growth of the positive electrode material and inhibit the generation of range defects. Meanwhile, as a carbon source, an N-element-doped carbon layer is formed in the carbonization process, so that the electronic conductivity of the material is improved, and the specific discharge capacity, the cycle performance and the rate capability of the olivine type positive electrode material are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion batteries, and in particular to the field of positive electrode materials for lithium ion batteries. Background Art

[0002] With the global emphasis on environmental protection and energy conservation, the new energy vehicle market is showing a rapid growth trend. The rapid growth in demand for new energy vehicles is one of the main driving forces for the growth of lithium battery applications. As the main power source for new energy vehicles, the demand for lithium batteries has also increased. As one of the world's largest new energy vehicle markets, China's production and sales have shown a rapid growth trend, further driving the demand for lithium batteries. As one of the mainstream positive electrode materials, the advantages of olivine-type positive electrode materials are mainly reflected in their low cost, long cycle, high safety and environmental friendliness. At the same time, olivine-type positive electrode materials also have inherent disadvantages, such as low lithium ion diffusion coefficient and poor electronic conductivity.

[0003] In order to solve the limitation of its electrochemical performance, the optimization is mainly carried out by reducing the grain size, coating the surface with a conductive layer and bulk doping modification. Specifically, reducing the grain size can greatly shorten the diffusion path of lithium ions, thereby enhancing the rate capability of the battery; coating the surface of the positive electrode material with a conductive coating can improve its electronic conductivity and promote electron transfer. In addition, the conductive coating helps protect the electrode material by preventing the positive electrode material from being corroded by the electrolyte. However, a single optimization strategy can no longer meet the improvement of its electrochemical performance. To this end, multiple strategies are usually required for coordinated optimization.

[0004] During the investigation, it was found that among various surfactants, hexadecyltrimethylammonium bromide (CTAB) is a cationic surfactant, which is widely used in the synthesis of inorganic nanoparticles, mesoporous silica, and as a catalyst for redox reactions. Jiang et al. successfully combined CTAB with alginate microgels to develop a new emulsifier with excellent emulsification ability (Food Hydrocolloids 2023, 140, No. 108607). Wu et al. synthesized CuS crystals using the CTAB-assisted synthesis method and achieved morphological control (Journal of Materials Science&Technology2013, 29,1047−1052). As a cationic surfactant, CTAB not only has the function of stabilizing the solution, but also can be used to achieve morphological modification of inorganic particles due to its hydrophilic head and hydrophobic tail. In addition, CTAB contains N elements, and the carbonization process will increase the concentration of defects and electron active sites.

[0005] Therefore, the present invention provides a coordinated optimization synergistic strategy using surfactant CTAB-induced bulk phase modification and novel carbon coating to jointly improve the electrochemical performance of olivine-type cathode materials. Summary of the invention

[0006] According to the technical background, the purpose of the present invention is to provide an olivine-type positive electrode material with a simple preparation method, easy to control the preferred crystal orientation and excellent electrochemical performance. Specifically, a preparation method for optimizing the olivine-type positive electrode material using the surfactant CTAB is provided, using CTAB as an inducer, and forming an optimized olivine-type positive electrode material through thermal reaction with raw material solvents such as Li, Mn, Fe, and P. In this method, the CTAB inducer can both induce the preferential growth of the crystal face and attach to the surface of the particles at the same time. In the subsequent processing process, it serves as a carbon source, and forms a carbon layer doped with N elements through carbonization, thereby increasing the electronic conductivity of the material. The two work together to make the final product have excellent electrochemical properties.

[0007] The method mainly includes the following steps: Step S1, adding Li source, Fe source, Mn source, P source and surfactant into a reactor according to proportion; Step S2, using water and diethylene glycol solution as solvents to perform a solvothermal reaction to obtain a precursor; Step S3, washing and drying the precursor; Step S4, mixing the precursor with an appropriate amount of carbon source and grinding them evenly; Step S5, placing the mixed powder obtained in S4 in a tubular furnace for sintering to obtain an olivine-type positive electrode material optimized by a surfactant.

[0008] Furthermore, the surfactant added in step S1 is cetyltrimethylammonium bromide (CTAB), and the added amount is 0-1 mmol.

[0009] Furthermore, in step S1, the ratio of Fe source to Mn source is controlled to be 0-1, and the molecular formula of the formed olivine-type positive electrode material is LiMn x Fe y PO 4 , where 0.5≤x≤1, 0≤y≤0.5.

[0010] Further, in step S1, the amount of Li source added is 30 mmol, the amount of P source added is 10 mmol, and the total mass of Fe source and Mn source is 10 mmol.

[0011] Furthermore, in step S2, the volume ratio of deionized water to diethylene glycol (DEG) is 1:2-1:2.3.

[0012] Furthermore, in step S4, the mixed carbon source is sucrose and PVDF, and the ratio is 1:2, and the total mass of the mixed carbon source is controlled to be 15 wt%~20 wt% of the positive electrode material.

[0013] Furthermore, in step S4, the sintering temperature is controlled and two-stage sintering is adopted, wherein the sintering temperature of the first stage is 250-450°C and the time is 2-5 hours; the sintering temperature of the second stage is 600-700°C and the time is 6-8 hours, and the gas is an argon-hydrogen mixed gas (95 / 5 vol%).

[0014] The advantages of the present invention are as follows: 1. The present invention uses CATB as an inducer to induce the morphology of the olivine-type cathode material and reduce the grain size during the solvothermal process, which helps to shorten the transmission distance of lithium ions and effectively improve the electrochemical performance of the olivine-type cathode material; 2. The present invention uses CATB as an inducing agent. During the solvothermal process, CTAB induces the olivine-type cathode material to grow along the (010) crystal direction, that is, the b-axis direction, reducing the Li + Resistance in diffusion of cathode materials; 3. Since CATB is an organic compound containing N, N doping will be formed in the carbon layer during the sintering process. The introduction of heteroatoms improves the electronic conductivity of the carbon layer, which further increases the electrochemical properties of the material; 4. The olivine-type cathode material prepared by the present invention exhibits an ultra-high specific capacity at 1C by adjusting the amount of CTAB added. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is the XRD spectrum of the positive electrode material prepared by the method described in Examples 1, 2, 3, 4, 5 and Comparative Example 1.

[0016] Figure 2 It is the FIIR spectrum of the positive electrode material prepared by the method described in Examples 1, 2, 3, 4, 5 and Comparative Example 1.

[0017] Figure 3 This is a SEM image of the positive electrode material prepared by the method described in Example 1.

[0018] Figure 4 It is a rate performance diagram of batteries assembled with the positive electrode materials prepared by the methods described in Examples 1, 2, 3, 4, 5 and Comparative Example 1 at different current densities. DETAILED DESCRIPTION

[0019] The following is a detailed description with reference to the accompanying drawings and specific implementation methods. Example 1

[0020] The Li source, Mn source and P source are LiOH·H 2 O、MnSO 4 ·H 2 O, H 3 PO 4 (85%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio R=V DEG :V H2O =2. 30 mmol LiOH·H 2 O, 10 mmol H 3 PO 4 , 10 mmolMnSO 4 ·H 2 O was placed in the mixed solution and stirred to form a stable emulsion; 0.05 mmol hexadecyltrimethylammonium bromide (CTAB) was added; the reactor was placed in a 200 °C forced air drying oven for hydrothermal reaction for 12 h. After the hydrothermal product was washed with ultrapure water and ethanol three times each, the precursor and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material, where sucrose: PVDF = 1:2) were placed in a mortar and ground for 30 min, and the powder was placed in a tube furnace and heated at 95 Ar / 5H 2 The material was pre-calcined at 300 °C for 2 h under a carbon atmosphere to mainly remove organic impurities and exclude the influence of air, then heated to 650 °C and kept for 5 h, and naturally cooled to room temperature to obtain a carbon-coated composite positive electrode material, which was recorded as LMP-0.05. Example 2

[0021] The difference from Example 1 is that the content of the added surfactant is changed to 0.1 mmol. The Li source, Mn source, and P source are LiOH·H 2 O、MnSO 4 ·H 2 O, H 3 PO 4 (85%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio R=V DEG :V H2O =2. 30 mmol LiOH·H 2 O, 10 mmol H 3 PO 4 , 10 mmol MnSO 4 ·H 2O was placed in the mixed solution and stirred to form a stable emulsion; 0.1 mmol hexadecyltrimethylammonium bromide (CTAB) was added; the reactor was placed in a 200°C forced air drying oven for hydrothermal reaction for 12 h. The hydrothermal product was washed with ultrapure water and ethanol three times each, and the precursor and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material, where sucrose: PVDF = 1:2) were placed in a mortar and ground for 30 min. The powder was placed in a tube furnace and heated at 95 Ar / 5H 2 The material was pre-calcined at 300 °C for 2 h under an atmosphere to mainly remove organic impurities and exclude the influence of air, then heated to 650 °C and kept for 5 h, and naturally cooled to room temperature to obtain a carbon-coated composite positive electrode material, which was recorded as LMP-0.1. Example 3

[0022] The difference from Example 1 is that the content of the added surfactant is changed to 0.2 mmol. The Li source, Mn source, and P source are LiOH·H 2 O、MnSO 4 ·H 2 O, H 3 PO 4 (85%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio R=V DEG :V H2O =2. 30 mmol LiOH·H 2 O, 10 mmol H 3 PO 4 , 10 mmol MnSO 4 ·H 2 O was placed in the mixed solution and stirred to form a stable emulsion; 0.2 mmol hexadecyltrimethylammonium bromide (CTAB) was added; the reactor was placed in a 200°C forced air drying oven for hydrothermal reaction for 12 h. After the hydrothermal product was washed with ultrapure water and ethanol three times each, the precursor and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material, where sucrose: PVDF = 1:2) were placed in a mortar and ground for 30 min, and the powder was placed in a tube furnace and heated at 95 Ar / 5H 2 The material was pre-calcined at 300 °C for 2 h under a carbon atmosphere to mainly remove organic impurities and exclude the influence of air, then heated to 650 °C and kept for 5 h, and naturally cooled to room temperature to obtain a carbon-coated composite positive electrode material, which was recorded as LMP-0.2. Example 4

[0023] The difference from Example 1 is that the content of the added surfactant is changed to 0.5 mmol. The Li source, Mn source, and P source are LiOH·H 2 O、MnSO 4 ·H 2 O, H3 PO 4 (85%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio R=V DEG :V H2O =2. 30 mmol LiOH·H 2 O, 10 mmol H 3 PO 4 , 10 mmol MnSO 4 ·H 2 O was placed in the mixed solution and stirred to form a stable emulsion; 0.5 mmol hexadecyltrimethylammonium bromide (CTAB) was added; the reactor was placed in a 200°C forced air drying oven for hydrothermal reaction for 12 h. The hydrothermal product was washed with ultrapure water and ethanol three times each, and the precursor and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material, where sucrose: PVDF = 1:2) were placed in a mortar and ground for 30 min. The powder was placed in a tube furnace and heated at 95 Ar / 5H 2 Under the atmosphere, the material was pre-calcined at 300 °C for 2 h to mainly remove organic impurities and exclude the influence of air, then the temperature was raised to 650 °C and kept for 5 h, and then naturally cooled to room temperature to obtain a carbon-coated composite positive electrode material, which was recorded as LMP-0.5. Example 5

[0024] The difference from Example 1 is that the content of the added surfactant is changed to 1 mmol. The Li source, Mn source, and P source are LiOH·H 2 O、MnSO 4 ·H 2 O, H 3 PO 4 (85%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio R=V DEG :V H2O =2. 30 mmol LiOH·H 2 O, 10 mmol H 3 PO 4 , 10 mmol MnSO 4 ·H 2 O was placed in the mixed solution and stirred to form a stable emulsion; 1 mmol of hexadecyltrimethylammonium bromide (CTAB) was added; the reactor was placed in a 200 °C forced air drying oven for hydrothermal reaction for 12 h. After the hydrothermal product was washed with ultrapure water and ethanol three times each, the precursor and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material, where sucrose: PVDF = 1:2) were placed in a mortar and ground for 30 min, and the powder was placed in a tube furnace and heated at 95 Ar / 5H 2The material was pre-calcined at 300 °C for 2 h under an atmosphere to mainly remove organic impurities and exclude the influence of air, then heated to 650 °C and kept for 5 h, and naturally cooled to room temperature to obtain a carbon-coated composite positive electrode material, denoted as LMP-1. Example 6

[0025] The difference from Example 1 is that the Mn / Fe ratio is changed to 9:1. The Li source, Mn source, Fe source, and P source are LiOH·H 2 O、MnSO 4 ·H 2 O, FeSO 4 7H 2 O, H 3 PO 4 (85%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio R=V DEG :V H2O =2. 30 mmol LiOH·H 2 O, 10 mmol H 3 PO 4 , 9 mmol MnSO 4 ·H 2 , 1 mmolFeSO 4 7H 2 O was placed in the mixed solution and stirred to form a stable emulsion; 0.05 mmol hexadecyltrimethylammonium bromide (CTAB) was added; the reactor was placed in a 200 °C forced air drying oven for hydrothermal reaction for 12 h. After the hydrothermal product was washed with ultrapure water and ethanol three times each, the precursor and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material, where sucrose: PVDF = 1:2) were placed in a mortar and ground for 30 min, and the powder was placed in a tube furnace and heated at 95 Ar / 5H 2 Under the atmosphere, pre-sintering was carried out at 300 °C for 2 h to mainly remove organic impurities and exclude the influence of air, and then the temperature was raised to 650 °C and kept for 5 h, and then naturally cooled to room temperature to obtain a carbon-coated composite positive electrode material. Example 7

[0026] The difference from Example 1 is that the Mn / Fe ratio is changed to 7.5:2.5. The Li source, Mn source, Fe source, and P source are LiOH·H 2 O、MnSO 4 ·H 2 O, FeSO 4 7H 2 O, H 3 PO 4 (85%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio R=V DEG :VH2O =2. 30 mmol LiOH·H 2 O, 10 mmol H 3 PO 4 , 7.5 mmol MnSO 4 ·H 2 , 2.5mmol FeSO 4 7H 2 O was placed in the mixed solution and stirred to form a stable emulsion; 0.05 mmol hexadecyltrimethylammonium bromide (CTAB) was added; the reactor was placed in a 200 °C forced air drying oven for hydrothermal reaction for 12 h. After the hydrothermal product was washed with ultrapure water and ethanol three times each, the precursor and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material, where sucrose: PVDF = 1:2) were placed in a mortar and ground for 30 min, and the powder was placed in a tube furnace and heated at 95 Ar / 5H 2 Under the atmosphere, pre-sintering was carried out at 300 °C for 2 h to mainly remove organic impurities and exclude the influence of air, and then the temperature was raised to 650 °C and kept for 5 h, and then naturally cooled to room temperature to obtain a carbon-coated composite positive electrode material. Example 8

[0027] The difference from Example 1 is that the Mn / Fe ratio is changed to 5:5. The Li source, Mn source, Fe source, and P source are LiOH·H 2 O、MnSO 4 ·H 2 O, FeSO 4 7H 2 O, H 3 PO 4 (85%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio R=V DEG :V H2O =2. 30 mmol LiOH·H 2 O, 10 mmol H 3 PO 4 , 5 mmol MnSO 4 ·H 2 , 5 mmolFeSO 4 7H 2 O was placed in the mixed solution and stirred to form a stable emulsion; 0.05 mmol hexadecyltrimethylammonium bromide (CTAB) was added; the reactor was placed in a 200 °C forced air drying oven for hydrothermal reaction for 12 h. After the hydrothermal product was washed with ultrapure water and ethanol three times each, the precursor and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material, where sucrose: PVDF = 1:2) were placed in a mortar and ground for 30 min, and the powder was placed in a tube furnace and heated at 95 Ar / 5H2 Under the atmosphere, pre-sintering was carried out at 300 °C for 2 h to mainly remove organic impurities and exclude the influence of air, and then the temperature was raised to 650 °C and kept for 5 h, and then naturally cooled to room temperature to obtain a carbon-coated composite positive electrode material. Comparative Example 1

[0028] Different from Example 1, no surfactant was added in this comparative example. The Li source, Mn source, and P source were LiOH·H 2 O、MnSO 4 ·H 2 O, H 3 PO 4 (85%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio R=V DEG :V H2O =2. 30 mmol LiOH·H 2 O, 10 mmol H 3 PO 4 , 10 mmol MnSO 4 ·H 2 O was placed in the mixed solution and stirred to form a stable emulsion; the reactor was placed in a 200 °C forced air drying oven for hydrothermal reaction for 12 h. The hydrothermal product was washed with ultrapure water and ethanol three times each, and the precursor and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material, where sucrose: PVDF = 1:2) were placed in a mortar and ground for 30 min. The powder was placed in a tube furnace and heated at 95 Ar / 5H 2 The material was pre-calcined at 300 °C for 2 h under an atmosphere to mainly remove organic impurities and exclude the influence of air, then heated to 650 °C and kept for 5 h, and naturally cooled to room temperature to obtain a carbon-coated composite positive electrode material, denoted as LMP-0. Comparative Example 2

[0029] Unlike Example 6, no surfactant was added in this comparative example. The Li source, Mn source, Fe source, and P source were LiOH·H 2 O、MnSO 4 ·H 2 O, FeSO 4 7H 2 O, H 3 PO 4 (85%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio R=V DEG :V H2O =2. 30 mmol LiOH·H 2 O, 10 mmol H 3 PO 4 , 9 mmol MnSO 4·H 2 , 1 mmolFeSO 4 7H 2 O was placed in the mixed solution and stirred to form a stable emulsion; the reactor was placed in a 200 °C forced air drying oven for hydrothermal reaction for 12 h. The hydrothermal product was washed with ultrapure water and ethanol three times each, and the precursor and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material, where sucrose: PVDF = 1:2) were placed in a mortar and ground for 30 min. The powder was placed in a tube furnace and heated at 95Ar / 5H 2 Under the atmosphere, pre-sintering was carried out at 300 °C for 2 h to mainly remove organic impurities and exclude the influence of air, and then the temperature was raised to 650 °C and kept for 5 h, and then naturally cooled to room temperature to obtain a carbon-coated composite positive electrode material. Comparative Example 3

[0030] Unlike Example 7, no surfactant was added in this comparative example. The Li source, Mn source, Fe source, and P source were LiOH·H 2 O、MnSO 4 ·H 2 O, FeSO 4 7H 2 O, H 3 PO 4 (85%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio R=V DEG :V H2O =2. 30 mmol LiOH·H 2 O, 10 mmol H 3 PO 4 , 7.5 mmol MnSO 4 ·H 2 , 2.5mmol FeSO 4 7H 2 O was placed in the mixed solution and stirred to form a stable emulsion; the reactor was placed in a 200 °C forced air drying oven for hydrothermal reaction for 12 h. The hydrothermal product was washed with ultrapure water and ethanol three times each, and the precursor and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material, where sucrose: PVDF = 1:2) were placed in a mortar and ground for 30 min. The powder was placed in a tube furnace and heated at 95 Ar / 5H 2 Under the atmosphere, pre-sintering was carried out at 300 °C for 2 h to mainly remove organic impurities and exclude the influence of air, and then the temperature was raised to 650 °C and kept for 5 h, and then naturally cooled to room temperature to obtain a carbon-coated composite positive electrode material. Comparative Example 4

[0031] Unlike Example 8, no surfactant was added in this comparative example. The Li source, Mn source, Fe source, and P source were LiOH·H2 O、MnSO 4 ·H 2 O, FeSO 4 7H 2 O, H 3 PO 4 (85%), the solvent is a mixture of diethylene glycol (DEG) and water, the solvent ratio R=V DEG :V H2O =2. 30 mmol LiOH·H 2 O, 10 mmol H 3 PO 4 , 5 mmol MnSO 4 ·H 2 , 5 mmolFeSO 4 7H 2 O was placed in the mixed solution and stirred to form a stable emulsion; the reactor was placed in a 200 °C forced air drying oven for hydrothermal reaction for 12 h. The hydrothermal product was washed with ultrapure water and ethanol three times each, and the precursor and 21% mixed carbon source (accounting for the mass fraction of the positive electrode material, where sucrose: PVDF = 1:2) were placed in a mortar and ground for 30 min. The powder was placed in a tube furnace and heated at 95Ar / 5H 2 Under the atmosphere, pre-sintering was carried out at 300 °C for 2 h to mainly remove organic impurities and exclude the influence of air, and then the temperature was raised to 650 °C and kept for 5 h, and then naturally cooled to room temperature to obtain a carbon-coated composite positive electrode material.

[0032] Figure 1 It is the XRD spectrum of the positive electrode material of the preparation method described in Examples 1, 2, 3, 4, 5 and Comparative Example 1, wherein 2Thate is the diffraction angle and Intensity is the peak intensity. The six groups of positive electrode materials are compared with the standard card JCPDS No.74-0375 and all meet the requirements of olivine-type positive electrode materials, belonging to the Pnmb space group. The six groups of positive electrode materials have strong diffraction peaks, indicating good crystallinity. The lithium ions of olivine-type positive electrode materials mainly diffuse along the b-axis. When the exposed crystal face is (010), the lithium ion transmission distance can be shortened. The larger the R (R=I(020) / I(311)) value, the larger the lithium ion diffusion coefficient. The R values ​​of the six groups of positive electrode materials are 0.97, 1.05, 1.07, 1.03, 1.11, and 0.98, respectively. With the addition of CTAB, the positive electrode material changes from the (311) crystal plane to the (020) crystal plane, and as the CTAB content continues to increase, it changes from the (020) crystal plane to the (311) crystal plane. From the Bragg diffraction equation, it can be seen that the (020) crystal plane spacing first increases and then decreases, so that the lithium ion diffusion resistance first decreases and then increases with the increase of CTAB content. The right amount of CTAB can reduce the reaction resistance and improve the lithium ion diffusion capacity.

[0033] Figure 2 It is the FIIR spectrum of the positive electrode material prepared by the method described in Examples 1, 2, 3, 4, 5 and Comparative Example 1, wherein Wave number is the wave number, Transmittance is the projection density, Red Shift is red shift, i.e., shift to a lower wave number, and Blueshift is blue shift, i.e., shift to a higher wave number. LiMnPO 4 In the structure [PO 4 ] will be affected by the PO bond of [LiO 6 ] octahedron and [MnO 6 ] octahedron, so the presence of Li / Mn antisite defects will affect the wave number of the PO-Mn bond stretching vibration peak. The higher the concentration of antisite defects in the crystal, the higher the wave number, and at the same time, a charge compensation effect will occur, and Mn occupies the 4a position to hinder the diffusion of lithium ions. Compared with the LMP-0 positive electrode material, with the increase of CTAB content, the material first red-shifts and then blue-shifts. When CTAB<0.2 mmol, the generation of antisite defects is suppressed, and the electronic conductivity is enhanced.

[0034] Figure 3 This is a SEM image of the positive electrode material prepared by the method described in Example 1. The addition of CTAB induces it to become regular flaky particles, with uniform particle size distribution and regular morphology, and an average size of about 50 nm. This is mainly because the CTAB structure is positively charged, which reduces the surface tension of the particles and forms a thin film on its surface, which can prevent excess Mn from being absorbed in the solution. 2+ The close proximity inhibits the growth of crystals and prevents contact between particles, thereby inhibiting agglomeration.

[0035] Figure 4 The figure shows the rate performance of the battery assembled with the positive electrode materials prepared by the methods described in Examples 1, 2, 3, 4, 5 and Comparative Example 1 at different current densities. Cycle number is the number of cycles and Specific capacity is the discharge specific capacity. After comparison, it was found that after CTAB modification, the discharge specific capacity of LMP-0.05 at different rates was 160.4, 157.3, 141.1, 128, 114.8, 98.2, 82.5 and 59.3 mAh g -1 The discharge specific capacity has been significantly improved. CTAB exposes the (010) crystal plane, shortens the transmission distance of Li, and makes the carbon layer uniform and moderate in thickness during the carbon coating process, providing a conductive network for the conduction of lithium ions and electrons, and having better electronic conductivity and diffusion coefficient.

[0036] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

[0037] Although the above describes the specific implementation methods of the present invention, it is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that various modifications or variations that can be made by those skilled in the art on the basis of the technical solution of the present invention without creative work are still within the scope of protection of the present invention.

Claims

1. A method for preparing an olivine-type cathode material using a surfactant, cetyltrimethylammonium bromide (CTAB), characterized in that: The method comprises the following steps: S1, adding Li source, Fe source, Mn source, P source and surfactant into the reactor according to the proportion; S2, using water and diethylene glycol solution as solvents for solvothermal reaction to obtain a precursor; S3, washing and drying the precursor; S4, mixing the precursor with an appropriate amount of carbon source and grinding them uniformly; S5, placing the mixed powder obtained in S4 in a tubular furnace for sintering to obtain an olivine-type positive electrode material optimized by a surfactant.

2. The method for preparing an olivine-type cathode material by using a surfactant as claimed in claim 1, characterized in that: The surfactant added in step S1 is cetyltrimethylammonium bromide (CTAB), and the added amount is 0-1 mmol.

3. The method according to claim 1, characterized in that In step S1, the ratio of Fe source to Mn source is controlled to be 0-1, and the molecular formula of the formed olivine-type positive electrode material is LiMn x Fe y PO4, where 0.5≤x≤1, 0≤y≤0.

5.

4. The method according to claim 1, characterized in that In step S2, the volume ratio of deionized water to diethylene glycol (DEG) is 1:2 to 1:2.

3.

5. The method according to claim 1, wherein: In step S4, the mixed carbon source is sucrose and PVDF, and the ratio is 1:2, and the total mass of the mixed carbon source is controlled to be 15 wt%~20 wt% of the positive electrode material.

6. The method according to claim 1, wherein: In step S4, the sintering temperature is controlled and two-stage sintering is adopted, wherein the sintering temperature of the first stage is 250-450°C and the time is 2-5 hours; the sintering temperature of the second stage is 600-700°C and the time is 6-8 hours, and the gas is an argon-hydrogen mixed gas (95 / 5 vol%).

Citation Information

Patent Citations

  • Preparation method of high-exposure (010) crystal face morphology lithium manganese phosphate positive electrode material

    CN116873893A

  • Modification method of high-voltage olivine-type lithium cobalt phosphate positive electrode material

    CN118458721A

  • Lithiated Manganese Phosphate and Composite Material Comprising Same

    US20140295281A1

  • Co-solvent assisted microwave-solvothermal process for making olivine lithium transition metal phosphate electrode materials

    US20150303473A1